2010
DOI: 10.1186/1743-0003-7-44
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diabetes and/or peripheral neuropathy in detecting short postural perturbations in mature adults

Abstract: BackgroundThis study explored the effects of diabetes mellitus (DM) and peripheral neuropathy (PN) on the ability to detect near-threshold postural perturbations.Methods83 subjects participated; 32 with type II DM (25 with PN and 7 without PN), 19 with PN without DM, and 32 without DM or PN. Peak acceleration thresholds for detecting anterior platform translations of 1 mm, 4 mm, and 16 mm displacements were determined. A 2(DM) × 2(PN) factorial MANCOVA with weight as a covariate was calculated to compare accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
1
29
0
5
Order By: Relevance
“…Our findings are similar to those of Fulk et al, 28 who reported differences only between individuals with and without DM2 and not between individuals with and without DN.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are similar to those of Fulk et al, 28 who reported differences only between individuals with and without DM2 and not between individuals with and without DN.…”
Section: Discussionsupporting
confidence: 94%
“…The heterogeneous results are suggestive of the effect of other factors on postural stability. Fulk and colleagues found that neuropathy might not be the only cause of impaired balance in people with diabetes mellitus and that diabetes itself might negatively impact the postural control system [Fulk et al 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should be aware that individuals with diabetes at an early stage of the disease process when they do not yet have peripheral neuropathy may have impaired balance, which may place them at risk for a fall. 13 The gait velocity, step length, amplitude of ankle movement, ankle moments of force, power and anterior-posterior ground reaction force variables are smaller in diabetic patients with polyneuropathy, compared to control subjects. 14 These findings agreed with our results as regards speed of the forward progression.…”
Section: Groupmentioning
confidence: 98%